Heterosis of Yield and Quality Traits of Watermelon [Citrullus lanatus var. lanatus (Thunb.)] Hybrids and Their Performance in the Sub-Tropical Region - Quamruzzaman, A K M; Akter, Limu; Salim, M M R; Islam, Ferdouse (European Journal of Applied Sciences, 2023)
A study was conducted in watermelon to estimate the magnitude of heterosis for yield and its nine yield-related components. Sixteen hybrids generated from eight diverged parents were evaluated in a Randomized Block Design with three replications at the Olericulture Division, Horticulture Research Center (HRC), Bangladesh Agricultural Research Institute (BARI), Gazipur, Bangladesh. Appreciable heterosis was found over better parents for all the traits studied in a desirable direction. The range of positive better parent heterosis for a number of fruits/plant and individual fruit weight was 4.50 to 30.56 percent and 7.17 to 21.05 percent, respectively, while for fruit length and fruit diameter, it was 0.63 to 11.47 percent and 2.74 to 14.40 percent, respectively. Nine hybrids showed significant positive heterotic response for TSS, while twelve hybrids for fruit yield showed positive better parent heterosis and the range was 9.38 to 51.17 %. The higher significant positive better parent heterosis was observed in hybrids F1 104 (51.17%), F1 105 (44.30%), F1 801 (29.45%), F1 102 (23.38%), F1 401 (19.74%), F1 103 (19.14%). Considering yield contributing characters, the hybrids viz., F1 102, F1 104, F1 105, F1 801 were found promising and may be recommended for hybrid watermelon variety for the farmers of sub-tropical countries.